IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS MULTIMEDIA UNTUK MENINGKATKAN PEMAHAMAN DAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PAI DI SMP NAMIRA - Zahro, Fatimatus; Syahda, Siti Latifa; Ni'mah, Lailatun (Universitas Al Falah As Sunniyah Kencong Jember (UAS Press), 2025)
The role of education in fostering high-quality human resources and equipping students with relevant skills is paramount. In the context of Islamic Education (PAI), the complexities of learning pose significant challenges, particularly in terms of instilling spiritual values and developing students' character. The advent of globalization and technological advancements has rendered multimedia an innovative tool in enhancing students' interest and understanding. Multimedia-based learning models facilitate active learning through a multifaceted combination of texts, audio, videos, and interactive animations. Empirical evidence suggests that this approach is efficacious in promoting learning motivation and comprehension of complex concepts in PAI subjects. Observations and interviews conducted at SMP Namira indicate that the integration of multimedia in PAI learning has yielded positive outcomes, including enhanced engagement, increased student participation, and improved understanding of the material. This study seeks to investigate the effectiveness of multimedia implementation in PAI learning and provide recommendations for future development.